GAYA KOMUNIKASI MASYARAKAT PESISIR WEDUNG JAWA TENGAH - Mahfudlah Fajrie (INJECT (Interdisciplinary Journal of Communication), 2017)
The coastal communities put human on equality. Therefore, Wedung district community has its own communication style in delivering opinions and social interaction interpersonally. This article is the result of field research study with an ethnographic approach and analysis of cultural themes. The aim is to determine the communication style of coastal communities when communicating with outside communities of coastal areas and tourists. The results show that the communication style of coastal communities in communicating with other people and the community outside of coastal areas is the equalitarian and the relinguishing styles. It means that the coastal communities have the nature of open communication and receptive to suggestions and opinions of others. AbstrakMasyarakat pesisir menempatkan manusia pada tingkat kesetaraan. Oleh sebab itu, masyarakat Kecamatan Wedung mempunyai gaya komunikasi sendiri dalam menyampaikan pendapatnya dan berinteraksi sosial dengan masyarakat lain. Artikel ini adalah hasil penelitian field research dengan pendekatan etnografi dan analisis tema kultural. Dengan tujuan untuk mengetahui gaya komunikasi masyarakat pesisir ketika berkomunikasi dengan masyarakat luar wilayah pesisir dan turis (wisatawan). Hasilnya menunjukkan gaya komunikasi masyarakat pesisir dalam berkomunikasi dengan masyarakat lain maupun masyarakat di luar wilayah pesisir adalah the equalitarian style dan the relinguishing style, artinya masyarakat pesisir dalam berkomunikasi mempunyai sifat terbuka dan mau menerima saran serta pendapat dari orang lain.